[RETRACTED] Pengaruh Modal Intelektual Terhadap Pertumbuhan Koperasi Di Kota Kupang - Zacharias, Jems Arison; Rosari, Renya (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2019)
The purpose of this study was to find a causal relationship between Intellectual Capital and the growth of cooperatives in Kupang City. Intellectual capital in this study was measured using Value Added Intellectual Coefficient (VAIC) while the growth of cooperatives was measured using changes in the natural logarithm of the cooperative's total assets. The population in this research were all cooperatives registered with the Kupang Cooperative and SME Office. The sample selection uses purposive sampling, namely cooperatives that have issued cooperative financial statements from 2011-2017. The test model applied includes descriptive statistics, classic assumption tests, simple and multiple regression analysis. The results showed that Intellectual Capital (which is proxied by VAIC) had an effect on the growth of cooperatives in Kupang City. But among the 3 components that make up VAIC, namely CEE (Capital Employed Efficiency), HCE (Human Capital Efficiency), and SCE (Structural Capital Efficiency), only CEE has a significant effect on the growth of cooperatives in Kupang City. This can be interpreted that in general cooperatives in Kota Kupang focus more on the growth of their business through efficient use of physical capital compared to improving the quality of their human resources.